(untitled) (Journal of Academic Research, 2024)
The purpose of the study was to focus on the statement of the expired lease contract in terms of: The study found that the expired lease was one of the newly emerging contemporary contracts, as a result of the applicant’s need for a commodity that was not currently affordable, as well as a secure means of security for the vendor, and provided tenants with the benefit of it without having to freeze capital if it existed. The researcher has made several significant findings, with the most noteworthy being the efficacy of the expired lease as an enhanced method for installment sales. However, it should be noted that the expired lease differs from traditional installment sales in that the transfer of ownership occurs subsequent to the expiration of the lease agreement. Additionally, the expired lease, when coupled with ownership, emerges as a crucial formula for fostering economic development. Regarding the search plan, it was organized into five investigations. The initial study focused on the definition and categorization of leases, specifically those that lead to ownership. The second investigation delved into the examination of financial leasing that leads to ownership within Islamic banks, along with its associated benefits. Lastly, the third investigation specifically highlighted the regulatory measures pertaining to lease contracts that result in ownership. The fourth investigation examines the economic advantages of lease contracts that culminate in ownership. The study analyzed the overall economic repercussions of the termination of financial lease contracts resulting in ownership, focusing on the fifth investigation. Subsequently, the most significant findings are presented.